Textual Equivalence of Cohesive Devices in Arabic-Indonesian Personal References - Mufidah, Shofiy Petrina; Masrukhi, Moh (Al-Lisan: Jurnal Bahasa, 2024)
The textual equivalence between the source text (ST) and the target text (TT) is greatly influenced by cohesive device translation. This article aims to analyze textual equivalence in translating personal references from Arabic to Indonesian. This research is a qualitative descriptive study using Halliday and Hasan's (1976) theory of cohesion and Baker's (2018) theory of cohesiveness in textual equivalence. The data came from the narrative discourse of the saga genre of the book 'Wali Tanah Jawa' in the form of the Arabic text "Ahla Al-Musamarah fi Hikayati Al-Auliya' Al-'Asyrah" by Sheikh Abul Fadhol Senori (1961) and the translation by M. Solahudin (2020). The results of the analysis showed that there were three findings in the translation of cohesive personal reference devices from Arabic into Indonesian, namely variations in the form of alignment of personal reference translators, differences in the frequency of appearance of personal references in equivalent language units, and the interrelationship of social and cultural relationship factors in the translation of personal references.